2018
DOI: 10.1016/j.soildyn.2018.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical modelling of buried pipelines crossing reverse faults

Abstract: Fault rupture is one of the main hazards for continuous buried pipelines and the problem is often investigated experimentally and numerically. While experimental data exists for pipeline crossing strike-slip and normal fault, limited experimental work is available for pipeline crossing reverse faults. This paper presents results from a series of tests investigating the behaviour of continuous buried pipeline subjected to reverse fault motion. A new experimental setup for physical modelling of pipeline crossing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 34 publications
(34 reference statements)
0
23
0
6
Order By: Relevance
“…An increasing seismic vulnerability of NG pipelines was actually reported on steel pipelines that were previously weakened by corrosion or poor quality welds (EERI, 1986;Gehl et al, 2014). Permanent ground deformations commonly induce a higher straining on the steel pipelines, compared to transient ground deformations; therefore, most research efforts have been mainly focused on this seismic hazard (Karamitros et al, 2007;Vazouras et al, 2010;Vazouras et al, 2012;Kouretzis et al, 2014;Vazouras et al, 2015;Vazouras et al, 2016;Karamitros et al, 2016;Melissianos et al, 2017aMelissianos et al, , 2017bMelissianos et al, , 2017cDemirci et al, 2018;Sarvanis et al, 2018,;Tsatsis et al 2018, among many others). However, statistically it is more likely for a pipeline to be subjected to transient ground deformations rather than seismically induced permanent ground deformations.…”
Section: Seismic Performance and Critical Failure Modes Of Buried Ng mentioning
confidence: 99%
“…An increasing seismic vulnerability of NG pipelines was actually reported on steel pipelines that were previously weakened by corrosion or poor quality welds (EERI, 1986;Gehl et al, 2014). Permanent ground deformations commonly induce a higher straining on the steel pipelines, compared to transient ground deformations; therefore, most research efforts have been mainly focused on this seismic hazard (Karamitros et al, 2007;Vazouras et al, 2010;Vazouras et al, 2012;Kouretzis et al, 2014;Vazouras et al, 2015;Vazouras et al, 2016;Karamitros et al, 2016;Melissianos et al, 2017aMelissianos et al, , 2017bMelissianos et al, , 2017cDemirci et al, 2018;Sarvanis et al, 2018,;Tsatsis et al 2018, among many others). However, statistically it is more likely for a pipeline to be subjected to transient ground deformations rather than seismically induced permanent ground deformations.…”
Section: Seismic Performance and Critical Failure Modes Of Buried Ng mentioning
confidence: 99%
“…e results showed that there was no significant difference between the responses of pipelines under the displacement of dynamic test and those under the static test. Demirci et al [5] conducted a series of experiments to analyze the behavior of continuous buried pipelines subjected to reverse fault motion and developed a novel experimental device for studying pipelines crossing reverse faults. Zhang et al [6] carried out a full-scale test to study the effect of soil settlement on the pipeline.…”
Section: Introductionmentioning
confidence: 99%
“…Permanent ground deformations tend to induce higher straining on buried steel pipelines, compared to transient ground deformations. Hence, most researchers focused their investigations on this seismic hazard [12][13][14][15][16][17][18][19][20][21][22][23]. However, it is more likely for a buried pipeline to be subjected to transient ground deformations rather than seismically-induced permanent ground deformations.…”
Section: Introductionmentioning
confidence: 99%